Fatores influentes no desempenho em regime de teletrabalho: estudo de caso na pandemia da COVID-19 - Wilhelms, Andreia (Universidade do Vale do Rio dos Sinos, 2022)
The implementation of the telework approach on emergence and crisis situations such as the pandemic context of COVID-19 represents a challenge for the survival and prospering of organizations in a complex business environment, as well as for workers who must adapt to the new working format. Despite the relevance of telework as alternative working method, there is an important fact to consider concerning how the work outside of the physical office affects worker’s performance. In this context, the current research’s general objective was to analyze what factors may influence the labor activities performance conducted on the teleworking modality during the pandemic of COVID-19 at the Alfa company. Initially, it was carried out a systematic literature review (SLR), in which it was identified thirty-nine factors that may influence the teleworker performance. Throughout the SLR results, it was applied the Delphi method on a group of ten specialists, which pointed out in consensus the level of influence of each factor. Furthermore, considering the objective to verify which factors may influence the performance of labor activities adopted at the teleworking modality, a case study was carried out at the Alfa company. The factors considered with bigger influence on the worker’s performance in telework modality were: the worker’s autonomy, the displacement and work trips and online meetings, which match the opinion of the specialists. In this context, the research carries out a convergence on the evaluation of performance factors by the interviewed concerning the statements of the specialists in 24 of the factors which may influence performance, representing 75% of all factors. Among these, 16 factors represent the organizational level and 8 represent individual perspectives. The other 8 factors were considered of minimum or inexistent level of influence by the interviewed on the Alfa company. However, it is possible to realize as a contribution of the current research the results of the work, which can be used as hypothesis for the development of new observations and applications on the conducted activities on the teleworking modality by part of organizations.
Keywords: Teletrabalho; Desempenho; COVID-19; home office; Trabalho remoto; Telework; Worker’s performance; Telecommuting; Remote work; ACCNPQ::Engenharias::Engenharia de Produção